Artykuł oryginalnyComparison of halothane and desflurane anaesthesia on shunt and selected haemodynamic parameters during thoracosurgical procedures - Machała, Waldemar; Szebla, Renata; Perdeus, Jakub; Obrzut, Damian; Śmiechowicz, Katarzyna; Rysz, Jacek; Mamełka, Beata (Archives of Medical Science, 2006)
Introduction: Anaesthesia for lung surgical procedures usually requires one lung ventilation (OLV). This procedure, which facilitates the surgery, is the cause of breathing and respiratory disorders. The anaesthetic agent used in the procedure may stop physiological reactions of the organism which are the consequences of OLV. The aim of the study was the comparison of influence of inhalation anaesthesia with halothane and desflurane on shunt and selected haemodynamic parameters. Material and methods: 52 patients in the first and second physical status degree according to ASA scale operated on for lung cancer (non-microcellular) with thoracosurgical procedures. The anaesthesia method – balanced: the combination of extradural or thoracic paravertebral anaesthesia (fentanyl) with general anaesthesia (oxygen + air) with halothane (HAL) or desflurane (DES). Anaesthetics administered at the concentration of 1 MAC. Shunt and haemodynamic parameters were monitored with a Swan-Ganz catheter. Results: the kind of anaesthetic used had no influence on shunt value. The shunt value underwent statistically significant increase after OLV was started, without however differences related to the anaesthetics used. Halothane triggered considerable decrease of SVR leading to hypotension. Both anaesthetics decreased left ventricular stroke work index (LVSWI) and the coronary perfusion pressure value and right ventricular stroke work index. Halothane did not cause any changes in pulmonary vascular resistance, which resulted in a lack of change in blood pressure in the pulmonary artery. In contrast, desflurane anaesthesia caused a statistically insignificant increase in PVR value which was accompanied by a statistically insignificant increase in blood pressure in the pulmonary artery. Conclusions: 1. Halothane and desflurane may both be used as anaesthetics with patients operated on with one lung ventilation (OLV); their influence on shunt is similar. 2. Halothane seems to be safer for anaesthetizing patients with pulmonary hypertension – its administration does not increase PVR value. 3. For patients with limited coronary vascular reserve, desflurane appears to be worth recommending. The less distinct influence on SVR than halothane results in the fact that the increase in arterial blood pressure does not trigger an increase in coronary perfusion pressure (risk of acute myocardial ischaemia).